Sarcopenia and frailty combined increases the risk of mortality in patients with decompensated cirrhosis. (July 2022) - Guo, Gaoyue; Li, Chaoqun; Hui, Yangyang; Mao, Lihong; Sun, Mingyu; Li, Yifan; Yang, Wanting; Wang, Xiaoyu; Yu, Zihan; Fan, Xiaofei; Jiang, Kui; Sun, Chao
Background: Both sarcopenia and frailty are prevalent in patients with decompensated cirrhosis and associated with negative outcomes. However, few studies investigated the impact of their coexistence on mortality. We aimed to evaluate the role of sarcopenia and frailty on survival in a cohort of hospitalized cirrhotics. Methods: This was an observational cohort study including 221 patients hospitalized for decompensated events. The cutoff for low skeletal muscle index (SMI) at the third lumbar vertebra level on computed tomography built by our previous work (male: SMI <46.96 cm 2 /m 2 ; female: SMI <32.46 cm 2 /m 2 ) was used for the diagnosis of sarcopenia. Individuals with a Frailty Index >0.38 were considered frail. The sample was divided into four groups: sarcopenia and frailty (SF); sarcopenia and non-frailty (SN); non-sarcopenia and frailty (NF); and non-sarcopenia and non-frailty (NN). Follow-up for survival lasted 2 years. Results: Sarcopenia and frailty were present in 21.7% and 14.5% of the patients, respectively. The frequency of frailty in the group of sarcopenic patients was significantly higher than in the patients without sarcopenia (27.1% versus 11%, p = 0.009). In the survival analysis, the SF group showed a higher hazard ratio (2.604 in model 1; 4.294 in model 2) for mortality when compared with the NN group. In addition, the concurrence of those two conditions does give rise to incremental risk for mortality when compared with the group with each disturbance separately, namely, the SN/NF group. Conclusion: In conclusion, cirrhotic patients with sarcopenia and frailty combined showed higher mortality risk.